2002
DOI: 10.1099/0022-1317-83-1-11
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary trends of the first hypervariable region of the hepatitis C virus E2 protein in individuals with differing liver disease severity

Abstract: Hepatitis C virus (HCV) exists as a complex swarm of genetically related viruses known as a quasispecies. Recent work has shown that quasispecies complexity and evolutionary rates are associated with the outcome of acute infection. Knowledge of how the virus population evolves at different stages of chronic infection is less clear. We have studied rates of evolution of the first hypervariable region (HVR1) of the E2 envelope protein in six individuals with disparate liver disease severity. These data show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 65 publications
1
24
1
Order By: Relevance
“…As severe pathology develops, the number of susceptible host cells is reduced and this can prevent invasion of further antigenic variants. The hypothesis that virus evolution can drive disease progression is supported further by the observation that the population diversity, as well as the ratio of amino acid changing to silent substitutions was higher in individuals with severe liver disease (Cabot et al, 2000;Curran et al, 2002). Similar patterns have been observed in studies of virus evolution following liver transplants in patients with mild and severe disease (Lyra et al, 2002).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…As severe pathology develops, the number of susceptible host cells is reduced and this can prevent invasion of further antigenic variants. The hypothesis that virus evolution can drive disease progression is supported further by the observation that the population diversity, as well as the ratio of amino acid changing to silent substitutions was higher in individuals with severe liver disease (Cabot et al, 2000;Curran et al, 2002). Similar patterns have been observed in studies of virus evolution following liver transplants in patients with mild and severe disease (Lyra et al, 2002).…”
Section: Discussionmentioning
confidence: 57%
“…While the chimpanzee data argue against a role of escape for virus persistence, this study does not address the role of escape for disease progression, which occurs over a much longer period of time. Curran et al (2002) reported a consistent accumulation of amino acid-changing substitutions in patients with mild liver disease. In patients with severe liver disease, however, they reported significantly lower rates of virus evolution.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…5 In patients with chronic HCV, several attempts have been made to associate the genetic heterogeneity of HCV with the clinical features of chronic infection, but this issue remains still controversial. [6][7][8][9] In the liver transplantation setting, some studies have also analyzed the effect of the heterogeneity in the envelope region of HCV, with discrepant results. 10,11 In contrast, the potential influence of viral variability in T-cell epitopes on the outcome of recurrent infection after transplantation has been explored only rarely.…”
Section: H Epatitis C Virus (Hcv) Infection Is Distributedmentioning
confidence: 99%